Fanon argelino : uma visão crítica do colonialismo francês além dos muros hospitalares - Loos, Nicollas Eichstaedt (2023)
The present work seeks to analyze and build a historical and social understanding about the work of the Martinican thinker Frantz Fanon. We seek to see the evolution of his bibliography as a medical professional within Algerian territory, an active member of the FLN and an activist of the Algerian cause during his exile in Tunisia. Sequence and contextualize her observations and ideas, presenting the different instances that existed until the development of her theory of violence and how she would eventually become one of the main spokespersons for the liberation movements of the so-called Third World. When placed within a historical perspective, his works bring to light his effort to develop theories from the work carried out on his main raw material: the colonized individual, highlighting the different policies implemented by the French colonial authorities with the objective of conquering, expropriate and alienate the lands, properties and culture of the Algerian people. Presenting the methods used by revolutionaries to organize and carry out the search for the liberation of their integrity and autonomy, mixing elements of philosophy, medicine, history and sociology, Fanon transformed the understanding of colonial realities, until then Eurocentric, through combat and that of development of the consciousness of belonging of those then deprived of the possibility of belonging.